Effect of increasing the organic loading rate on the co-digestion and mono-digestion of cattle slurry and maize - Cornell, M (Water science and technology : a journal of the International Association on Water Pollution Research, 2012)
Co-digestion of cattle slurry and maize has been shown to have benefits for both, improving the biogas yield of the slurry and stability of digestion of the maize. The effect of increasing the total loading rate from 3 to 6 g VS l(-1) day(-1) on the co-digestion of cattle slurry and maize, mixed at equal volatile solids volumes, was investigated in laboratory-scale continuously stirred digesters. These were compared with similar digesters evaluating the increase of 1.5 to 3 g VS l(-1) day(-1) loading rates of slurry and maize digested separately. Compared with mono-digestion of the substrates, where the digestion of maize failed at loading rates greater than 2.5 g VS l(-1) day(-1), the co-digestion of cattle slurry and maize was feasible at all the loading rates tested with an increase in the volumetric methane yield occurring with loading rate. Even at the lowest rate of loading, the addition of equal amounts of volatile solids of maize to slurry leads to an increase in volumetric methane yield of 219%